The North Korean dilemma detering the undeterrable - Walid Lemrini-Abdi (2018)
The North Korean leadership has since the end of the Korean War in 1953 sustained a narrative of opposition to the U.S., its allies, and shut itself away from the international community. Observing the ever-enlarging military gap between the North and the South supported by the U.S., the regime has developed nuclear and ballistic missile capabilities which it has seen as crucial to the regime's survival. In recent years, repeated nuclear tests and ballistic missile launches which have threatened the stability of the Asia-Pacific region have led to stark episodes of tensions with the U.S., and its two allies Japan and South Korea. In its approach to North Korea, the current Trump administration has toughened its discourse on American deterrence, emphasising on American retaliation capabilities and calling for further international sanctions against Pyongyang. Nevertheless, American, allied, and international approaches to the North Korean nuclear agenda have not succeeded in preventing the current Kim administration from adopting an aggressive posture and enhancing its nuclear capabilities. In this respect, it is argued in this dissertation that the U.S., and the states concerned by North Korea's nuclear capabilities must understand that it is not possible to prevent the regime from achieving its nuclear agenda. Nonetheless, the U.S. and its allies have the resources to deter North Korea from adopting an aggressive posture and brandish its capabilities in a reckless manner. As such, deterrence which the U.S. implements for the most part, must set up clear and realistic objectives. Furthermore, American military strategists and policy-makers should consider North Korea's strategic culture. Here, the concept of strategic culture has the potential to inform the implementation of deterrence based on a deeper understanding of the rationale behind the regime's nuclear agenda. In considering North Korea's strategic culture, deterrence becomes better tailored to the particularities of the regime, having for effect to increase the odds of deterrence success. Keywords: North Korea, U.S., Deterrence, Deterrence by Punishment, Deterrence by Denial, Tailored Deterrence, Strategic Culture, Trump, Kim Jong-Un, Nuclear Capabilities, Blockchain